Aktivitas Harian Bekantan (Nasalis larvatus Wurmb) di Hutan Karet Kabupaten Tabalong, Kalimantan Selatan - Soendjoto, Mochamad Arief; Alikodra, Hadi Sukadi; Bismark, Muhammad; Setijanto, Heru (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2006)
The daily activities of the proboscis monkey (Nasalis larvatus Wurmb) living inrubber forests are poorly understood. The objectives of the research were to studyits daily movement pattern and to determine the time proportion of daily behaviors.The movement of the monkeys was followed by researchers on foot. The behaviorswere observed by scan technique in 15 second intervals for 30 minutes. In rubberforests, lowlands (baruh) were places where the monkey began and ended dailymovements and also conducted most activities. Most inter-water movements of themonkey (about 70%) were conducted twice a day. Statistically, movement distanceand rainfall were negatively and significantly correlated (Ò‘s = -0.58; p < 0.05; n = 14).The monkey spent more time for feeding in the morning and afternoon, and restingat midday. Most behaviors of feeding, resting, playing, and grooming (84.01%) wereconducted at a tree height of less than 15 m. The monkeys moved farther during thedry season to get water and did activities in accordance with height strata to getvarious foods, avoided disturbances, and got comfortable and safe places.